Baseline‐ and treatment‐associated pain in the X:BOT comparative effectiveness study of extended‐release naltrexone versus buprenorphine‐naloxone for OUD. (7th December 2021) - Wang, An‐Li; Shulman, Matisyahu; Choo, Tse‐Hwei; Pavlicova, Martina; Langleben, Daniel D.; Nunes, Edward V.; Rotrosen, John
Abstract: Chronic pain is highly prevalent among patients with opioid use disorder (OUD). However, little is known about how pharmacological treatments for OUD, for example, extended‐release naltrexone (XR‐NTX) and buprenorphine‐naloxone (BUP‐NX), affect pain. To begin addressing this question, we performed a secondary analysis of pain data on a large prospective 24‐week, open‐label, randomized‐controlled comparative effectiveness trial of XR‐NTX versus BUP‐NX (X:BOT trial). Participants' pain status was measured by the EuroQol (EQ‐5D). Based on their responses to the pain question at baseline, participants were dichotomized into "Pain" versus "No Pain" categories. Participant's pain status was evaluated every 4 weeks. A mixed effects longitudinal logistic regression model was fitted to examine the differential effect of XR‐NTX versus BUP‐NX on pain, modelling pain at all available follow‐up assessments, adjusted for age, sex, and baseline pain. A total of 474 individuals who were successfully inducted onto their assigned medications were included in this analysis. Among participants endorsing pain at baseline, substantial reductions in pain were observed over the course of the study in both treatment groups. Howecver reduction in pain was slightly greater in the group treated with XR‐NTX than the one treated with BUP‐NX (OR = 1.60 [95% CI: 1.07–2.40], P = 0.023). Future research using instruments and design specifically focused on pain could extend the present observations and evaluate their clinical significance. Abstract : Both XR‐NTX and BUP‐NX treatments were associated with reduced pain among the OUD patients reported pain at enrollment. Our finding that XR‐NTX was associated with better pain outcomes than was BUP‐NX contradicts a common assumption that opioid receptor blockade exacerbates pain.